(untitled) (Research, Society and Development, 2020)
The Serra da Tiririca State Park (PESET) RJ welcomed approximately 155,000 visitors in 2018. Such number of visitors cause anthropic impacts in the park. Considering the conservation of biodiversity and the maintenance of environmental services that the parks bring to the population, we carried out a survey of the anthropic impacts of PESET, through visits to the park and interviews with visitors and park employees. Between 2017 and 2018, 449 interviews were conducted with visitors and 28 with park staff to obtain the visitor profile and the activities developed by them during their visit. Most visitors were from the cities of Rio de Janeiro and Niterói (95%), had an incomplete university degree or higher (68%) and used to visit the park mostly on weekends and holidays (72%). Most visitors neither scheduled an appointment (91%) nor knew the park rules (72%). Contact with nature (44%) and sport activities (26%) were the main reasons to visit the park. Visitors with higher education levels and motivated by contact with nature, practice of sports, and religious activities reported less negative impacts to the park (p< 0.0001). The use of shortcuts and the discard/presence of solid waste were the most observed/reported impact. We recommend actions of environmental education combined with sport activities for the visitors, mainly on weekends and holidays. These must highlight the importance of knowing and respective the park’s rules. It is important that management plans include visitor’s characterization and that their profile is periodically monitored as part of an adaptive management plan.